2005
DOI: 10.1002/mas.20060
|View full text |Cite
|
Sign up to set email alerts
|

The negative ion chemistry of nitric oxide in the gas phase

Abstract: Nitric oxide is not only an important biological molecule with varied indispensable physiological roles but also shows interesting chemical reactivity both in gas-phase and solution phase. Even though it is a small molecule with an extremely low electron affinity, the reactivity of NO in the gas-phase is not just limited to electron-transfer or adduct formation. NO can behave both as an electrophile with closed-shell anions or as a radical with open-shell anions. Its reactivity with open-shell anions is charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 118 publications
3
11
0
Order By: Relevance
“…The addition reaction that occurs with 3p is consistent with what is expected for the closed-shell, imide anion . In contrast, the N–O exchange reaction has been observed previously with nitrene radical anions and is interpreted as indicating an open-shell electronic structure . Consequently, our previous study indicates that while 3p has a robust ground-state singlet, 2p is either a ground-state triplet or a singlet with a thermally accessible triplet state …”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…The addition reaction that occurs with 3p is consistent with what is expected for the closed-shell, imide anion . In contrast, the N–O exchange reaction has been observed previously with nitrene radical anions and is interpreted as indicating an open-shell electronic structure . Consequently, our previous study indicates that while 3p has a robust ground-state singlet, 2p is either a ground-state triplet or a singlet with a thermally accessible triplet state …”
Section: Introductionsupporting
confidence: 87%
“…56 In contrast, the N−O exchange reaction has been observed previously with nitrene radical anions 57 and is interpreted as indicating an open-shell electronic structure. 58 Consequently, our previous study indicates that while 3p has a robust ground-state singlet, 2p is either a ground-state triplet or a singlet with a thermally accessible triplet state. 55 A low-lying triplet state for 2p is somewhat surprising considering that it is isoelectronic with p-benzoquinone, 1p, which is a singlet with a large (>2 eV) singlet−triplet splitting.…”
Section: ■ Introductionmentioning
confidence: 96%
“…With closed-shell anions, it can react as an electrophile, and addition is commonly observed. 59,60 However, because it is also a free radical with a very low electron affinity, 61 it is able to undergo radical reactions without competing electron transfer, and often exhibits characteristic reactivity with open-shell anions. 62−67 For example, phenylnitrene radical anions, including PN −68 and even the methylphenylnitrene [M−N 2 ] − radical anions formed in this work, react with NO by nitrogen−oxygen exchange to form the corresponding phenoxides.…”
Section: ■ Discussionmentioning
confidence: 99%
“…2 , Bowen and co-workers [16,17] (see also their recent work [18] and the review [19] by Chacko and Wenthold) concluded that the trinitrogen dioxide anion admits several isomeric forms. Before focusing on the latter issue that in fact, as we believe, leads to resolving the N 3 O À 2 paradigm, let us mention that the DPS can provide some insight into the structural and energetics motifs of a molecular anion and the dissociative states of the corresponding neutral species.…”
Section: Experimental Puzzlesmentioning
confidence: 99%